The Effect of the Number of Clinical Bracket Points on the Accuracy of Curve Fitted to Dental Arch Form by 3D Method - Mahtab Nouri; Arash Farzan; Mohammad reza Safavi; Ali reza Akbarzadeh Baghban (Islamic Dental Association of Iran, 2012)
Background and Aim : Adjustment of an accurate curve to the dental arch is an important part of orthodontic treatment. Our goal was comparing the fitting accuracy of two curves constructed by different numbers of clinical bracket points (CBP) to the dental arch form using 4th degree polynomial function.   Materials and Methods : A mathematical formula associated with a polynomial function was used to reconstruct the dental arch forms of 18 adolescents (18 casts) with normal occlusion. CBPs were marked on every tooth present in each maxillary and mandibular model (second molar to second molar) using an orthodontic bracket positioning gauge. A coordinate measuring machine (CMM) was used to record the coordinates of each CBP (x, y). Then a curve fitting software was used to obtain the best 4th degree polynomial function and the associated curve fitted to all 14 CBPs. Another polynomial 4th degree function curve was obtained for the same models using CBPs only on central incisors, canines and second molars. Curves for each model were compared using statistical values including correlation coefficient, standard error, sum of residuals and R^2.   Results: The mean root squares for curves fitted to 14 points in all samples were 0.8855 and it was 0.9629 when 6 points were compared with 14 points . The intraclass correlation coefficient (ICC) between curves fitted to 6 and 14 points was 0.946 in mandible, 0.983 in maxilla and 0.969 for both .   Conclusion : Six CBPs were enough for proper fitting of 4th degree polynomial function to dental arch forms of both jaws .